Research on the relationship between the formation of local construction culture and geographical environment based on adaptability analysis - Tianbin Mao; Qian Li (Journal of King Saud University: Science, 2023)
Objectives: Since the natural ecology and geographical environment are the basis for the formation of local architecture, based on the adaptability analysis, the article analyzes the natural ecology and geographical environment that affect the creation of regional local architecture, and analyzes the adaptability of traditional architecture to natural ecology and the impact of traditional culture. Methods: The summary of the response methods is to try to find the substantive connotation of vernacular architecture in order to provide basic theoretical support for contemporary vernacular architecture creation. At the same time, combined with the characteristics of the times of the contemporary area, it proposes a typical site design adaptability analysis, a suitability climate adaptability analysis and a construction adaptability analysis returning to the local culture. And for the coastal cultural and historical background of the region, the development of regional ancient towns is discussed, and the location of regional coastal ancient towns is analyzed for the coastal environment. Results: The final selected model was a weighted average based on Akaike weights of 71 logistic candidate models that included all the variables in these 71 candidate models. The importance weights of variables are the criteria for assessing the impact and contribution rate of environmental factors on survival and dispersal, and are the sum of the Akaike weights of all candidate models containing a given predictor variable. The connection between households basically uses the scattered water of the building, does not occupy the foundation, and basically does not damage the landform. The entrance to the building is determined by the terrain on the one hand, and the road on the other, and is generally set on one side of the road. Finally, the coastal environmental background and historical and cultural background of regional ancient towns are summarized, and the research roughly explores the region. Conclusions: At the end of the article, through the interpretation of actual cases, it provides certain evidence and explanations for adaptability analysis, and expresses the design ideas of comprehensive trade-offs in the process of adaptability analysis, in order to provide contemporary local architectural design for the extensive urban and rural construction in the region with theories and adaptability analysis.